CORRELATIONS BETWEEN ELECTRICAL RESISTIVITY AND GEOTECHNICAL DATA IN SLOPE STABIITY ANALYSIS: A CASE STUDY AT PADALARANG SUB DISTRICT IN WEST JAVA - Phanjaya, Hermawan
Slope stability is common criterion used to evaluate landslide hazards. In slope stability study, internal structure and geotechnical properties is a pre-requisite in slope stability analysis. Many researchers have used a combination of geoelectrical and geotechnical measurements in slope stability analysis and obtained satisfactory results. However, the obtained results can only be explained qualitatively without any quantitative correlation. By forming a unique correlation between electrical resistivity data and geotechnical parameters, the rock strength can be estimated from the electrical resistivity data without the need for rock sampling. In this study, correlation between electrical resistivity and geotechnical data was used to study the slope stability in Padalarang sub-district, West Java. Geoelectrical method consisting of 3 Vertical Electrical Sounding (VES) points and 4 Electrical Resistivity Tomography (ERT) profile and geotechnical method which include 4 geotehcnical drilling along with the Standard Penetration Test (SPT) and laboratory measurement have been conducted in this area. Geoelectrical data were processed with inversion technique to reveal susbsurface resistivity distribution. Geotehcnical drilling results were used to interpreted subsurface resistivity results. Geotechnical drilling reveals 3 lithological unit that is silty clay, gravelly clay, and andesite breccia. Correlation between resistivity with SPT and geotechnical properties such as density, cohesion, and friction angle has been made. No clear quantitative correlation between SPT and resistivity extracted from ERT. Silty clay material showed correlation coefficient of 0.441, 0.9546, and 0.34 for its resistivity and density, cohesion, and friction angle respectively; means that density and cohesion parameters can be estimated from electrical resistivity data. An accurate geotechnical model were generated from integration of ERT and geotechnical results. This model was made to A-A’ and B-B’ line with well-defined boundary used for studying the slope stability analysis. Three scenarios were made by varying geotechnical properties of silty clay were used in this research, the first is usingiv averaged value from drilling, the second is using properties which the drilling was located at the line, and third scenario using the obtained correlation equation to convert into its geotechnical properties. Based on those scenarios, correlation between electrical resistivity and geotechnical data could help to roughly estimaste slope stability analysis based on the geoelectrical measurement.